2016
DOI: 10.1111/1751-2980.12383
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of corticosteroids for patients with severe drug‐induced liver injury

Abstract: Corticosteroids are not detrimental to DILI, but instead ameliorate liver injury and improve patient survival. Short-time use of corticosteroids is strongly recommended for severe DILI patients with hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
(52 reference statements)
1
45
0
Order By: Relevance
“…15 As a potent anti-inflammatory agent, glucocorticosteroids used for the treatment of ALF have been investigated with various outcomes. Studies in Asian populations commonly reported a more favorable outcome than those conducted in Western populations, [6][7][8] possibly due to the differences in ethnicity, background liver disease and precipitating events. Nevertheless, the inclusion criteria and treatment strategies also varied widely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 As a potent anti-inflammatory agent, glucocorticosteroids used for the treatment of ALF have been investigated with various outcomes. Studies in Asian populations commonly reported a more favorable outcome than those conducted in Western populations, [6][7][8] possibly due to the differences in ethnicity, background liver disease and precipitating events. Nevertheless, the inclusion criteria and treatment strategies also varied widely.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of ACLF is intensive systemic inflammation like sepsis . Corticosteroids are known to suppress the inflammatory process and have been demonstrated to reduce mortality in patients with acute liver failure (ALF) but not in others . The variation might be attributed to the differences in inclusion criteria, precipitating events, ethnic background and life‐supporting strategies among different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Available data also suggested that corticosteroids are invalid for DILI patients with ALF. We re‐analyzed data from the drug‐induced ALF cases in our study and also found that corticosteroid administration did not alter the prognosis for those patients with ALF . Consequently, the most appropriate candidates for corticosteroid treatment might be the patients with severe DILI who are prone to develop ALF.…”
Section: Dili Candidates Who May Benefit From Corticosteroid Therapymentioning
confidence: 82%
“…On the contrary, several investigations did show the beneficial effect of corticosteroids in DILI patients . Hou et al retrospectively collected data from 70 DILI patients with hepatocellular injury type and TB ≥10 × the upper limit of normal (ULN), of whom 20 received corticosteroid step‐down therapy.…”
Section: Efficacy Of Corticosteroid Treatment In Dili: Pros and Consmentioning
confidence: 99%
See 1 more Smart Citation